Measurement of the D± production asymmetry in 7 TeV pp collisions - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
The asymmetry in the production cross-section σ of D± mesons,AP=σ(D+)−σ(D−)σ(D+)+σ(D−), is measured in bins of pseudorapidity η and transverse momentum pT within the acceptance of the LHCb detector. The result is obtained with a sample of D+→KS0π+ decays corresponding to an integrated luminosity of 1.0 fb−1, collected in pp collisions at a centre of mass energy of 7 TeV at the Large Hadron Collider. When integrated over the kinematic range 2.0<pT<18.0 GeV/c and 2.20<η<4.75, the production asymmetry is AP=(−0.96±0.26±0.18)%. The uncertainties quoted are statistical and systematic, respectively. The result assumes that any direct CP violation in the D+→KS0π+ decay is negligible. No significant dependence on η or pT is observed.
Im Titel ist "±" ist hochgestellt
Available online19 November 2012
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 588
Gesehen am 23.04.2021